Preliminary Phytochemical Screening and Blood Glucose Lowering Activity of Methanol Extract of Salvia tilifolia Vahl aerial part - Sibhat, G G (International Journal of Pharmaceutical & Biological Archive, 2015)
Preliminary Phytochemical Screening and Blood Glucose Lowering Activity of Methanol Extract of Salvia tilifolia Vahl aerial part